2010
DOI: 10.3758/app.72.6.1576
|View full text |Cite
|
Sign up to set email alerts
|

A hit-and-miss investigation of asymmetries in wheelchair navigation

Abstract: In contrast to the leftward inattention caused by right parietal damage, normal brain function shows a subtle neglect of the right and left sides in peripersonal and extrapersonal space, respectively. This study explored how these attentional biases cause healthy individuals to collide with objects on the right. In Experiment 1, participants navigated manual and electric wheelchairs through a narrow doorway. More rightward collisions were observed for the electric, but not the manual, wheelchair. Experiment 2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
49
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(57 citation statements)
references
References 59 publications
(92 reference statements)
7
49
1
Order By: Relevance
“…A bias towards rightward collisions has been observed under laboratory conditions when participants walk through a narrow doorway [22], [23]. This asymmetry in collisions is not limited to ambulatory tasks and has also been found for the operation of electric wheelchairs [24].…”
Section: Introductionmentioning
confidence: 64%
See 1 more Smart Citation
“…A bias towards rightward collisions has been observed under laboratory conditions when participants walk through a narrow doorway [22], [23]. This asymmetry in collisions is not limited to ambulatory tasks and has also been found for the operation of electric wheelchairs [24].…”
Section: Introductionmentioning
confidence: 64%
“…Roberts and Turnbull [25] observed an association between line bisection and deviation in putting. While an association between different measures of attentional asymmetry is sometimes observed [23], a number of studies have found no effect [24], [27]. The association between the two-goal kicking and pointing data were examined with a correlational analysis.…”
Section: Introductionmentioning
confidence: 99%
“…The deviation was due to the shoulder rotation itself and the lateral sway of the body while walking [2]. The deviation was also due to lateralized spatial attention when approaching and crossing an aperture, which could cause deviation of the body midline toward the opposite of the attended side [2], [16], [20], [21]. It seemed likely that a relatively large safety margin (about 6–10 cm, Figure 3) was created so that such body deviation was taken into account.…”
Section: Discussionmentioning
confidence: 99%
“…Such a functional relationship was observed even when participants were tested in a virtual reality [8], when running through apertures [4], or when older adults were tested [11]. Furthermore, other gait and posture modifications when navigating through apertures, such as changes in speed [2], [12], [13], [14] or the magnitude of deviation of the body-midline from the center of the apertures [2], [15], [16], were also well proportioned to the ratio value. These findings lead researchers to a general understanding that the perception of the ratio value be important to control gait and posture for navigating through apertures [1], [2], [6], [12].…”
Section: Introductionmentioning
confidence: 86%
“…Not only scaling body rotation angles but also other locomotor modifications when navigating through openings, such as changes in speed (Higuchi et al, 2006a; Cinelli et al, 2008; Cowie et al, 2010; Fajen and Matthis, 2011) or the magnitude of deviation of the body midline from the center of the apertures (Higuchi et al, 2006a; Nicholls et al, 2010; Fujikake et al, 2011), were also well proportioned to this critical ratio value. These findings lead researchers to a general understanding that the perception of the ratio value be important to control gait and posture for navigating through apertures (Warren and Whang, 1987; Wagman and Taylor, 2005; Higuchi et al, 2006a; Fajen and Matthis, 2011).…”
Section: Perception Of Environment In Relation To Action Capabilitiesmentioning
confidence: 99%